Evaluación técnico financiera de la viabilidad de la implementación de un sistema de generación de energía eléctrica que permita el aprovechamiento del gas asociado al Campo Orito, Putumayo (2019)
Gas burning is one of the current energy challenges facing the world which is directly associated with environmental problems, whether regional or global, this also represents a multi-million dollar expense; resulting as a global energy problem which has persisted for decades. The World Bank has estimated that the annual volume of associated gas that is being burned and vented is around 110 billion cubic meters (BMC), which is enough fuel to meet the annual energy consumption of Germany and France. The study conducted for the Orito Field, is focused on the needs of the country today, where it is necessary to meet the energy needs of all regions; taking into account that when producing an energy resource in these areas it is imperative that full use be made of its potential for the benefit of all; Due to the above, it is intended to find a viable alternative for the use of this resource, evaluating that, the use of gas can be directed to the generation of electrical energy, in order to achieve the self-supply of some wells in the Field.